Applying community-based participatory research methods to improve maternal and child health in Karachi, Pakistan - Karmaliani, Rozina; McFarlane, Judith; Asad, Nargis; Madhani, Farhana; Hirani, Saima; Shehzad, Shireen; Zaidi, Anita (Nursing outlook, 2009)
To achieve health for all, the development of partnerships between community residents and researchers is essential. Community-based participatory research (CBPR) engages community members, uses local knowledge in the understanding of health problems and the design of interventions, and invests community members in the processes and products of research. CBPR pivots on an iterative process of open communication, mutual respect, and power sharing to build community capacity to sustain effective health interventions. This article describes how the tenets of CBPR were applied by a multidisciplinary, international research team of maternal-child health specialists toward better health for women and children in multilingual, multiethnic, low socioeconomic communities in Karachi, Pakistan.